Cardio-Oncology Rehabilitation: Strategies for Cardiovascular Risk Reduction and Recovery in Cancer Survivors - Michnowska, Wiktoria; Pustuła, Paweł; Szplit, Ewa; Hebda, Patryk; Błaszkowski, Bartłomiej; Cemaga , Roman; Król , Maria; Wolski, Adam; Kubicki , Mateusz; Więckowska , Katarzyna (Quality in Sport, 2026)
Background: Improved cancer survival has increased the number of survivors at risk of cardiovascular disease due to therapy-related cardiotoxicity. Pharmacological treatment alone often fails to address cardiovascular and functional impairments. Cardio-oncology rehabilitation (CORE) combines structured exercise with comprehensive cardiovascular risk management. Aim: To summarize current evidence on the role of CORE in cardiovascular risk reduction and functional recovery in cancer survivors exposed to cardiotoxic therapies. Materials and methods: A narrative review of PubMed, Scopus, and Google Scholar was performed, including randomized trials, observational studies, systematic reviews, meta-analyses, guidelines, and consensus documents focusing on adult cancer survivors. Results: Cancer survivors frequently exhibit elevated cardiovascular risk and reduced cardiorespiratory fitness. Exercise-based CORE programs consistently improve fitness, functional capacity, fatigue, and quality of life, with emerging benefits for cardiometabolic risk factors and vascular function. Evidence for reduced major cardiovascular events remains limited, although higher physical activity is associated with improved survival. Digital and hybrid CORE models appear feasible. Conclusions: CORE represents an effective strategy to enhance cardiovascular health and functional recovery in cancer survivors, though large trials are needed to confirm long-term outcomes.